Corporate Governance and Firm Free Cash Flows: Evidence from Malaysia - Adinehzadeh, Razieh (Information Management and Business Review, 2013)
This study provides view of free cash flow and corporate governance (CG) by addressing the relationship between audit committee characteristics with free cash flow. Specifically, this study explores whether audit committee characteristics are substitutes to control agency problem regarding to free cash flow within Malaysian firms. The data set comprise of 200 firm observations Malaysian companies for four consecutive years, which comprise of 2005 to 2008. The results show that size of audit committee, frequency of audit committee meeting, proportion of audit committee independence is positively associated with level of free cash flow (FCF). The results of study highlight the importance of corporate governance mechanism, in the form of audit committee characteristics, in the management of cash flow.